Genomic Comparison and Population Diversity Analysis Provide Insights into the Domestication and Improvement of Flax - Zhang, Jianping; Qi, Yanni; Wang, Limin; Wang, Lili; Yan, Xingchu; Dang, Zhao; Li, Wenjuan; Zhao, Wei; Pei, Xinwu; Li, Xuming; Liu, Min; Tan, Meilian; et al. (iScience, 2020)
Flax has been cultivated for its oil and fiber for thousands of years. However, it remains unclear how the modifications of agronomic traits occurred on the genetic level during flax cultivation. In this study, we conducted genome-wide variation analyses on multiple accessions of oil-use, fiber-use, landraces, and pale flax to identify the genomic variations during flax cultivation. Our findings indicate that, during flax domestication, genes relevant to flowering, dehiscence, oil production, and plant architecture were preferentially selected. Furthermore, regardless of origins, the improvement of the modern oil-use flax preceded that of the fiber-use flax, although the dual selection on oil-use and fiber-use characteristics might have occurred in the early flax domestication. We also found that the expansion of MYB46/MYB83 genes may have contributed to the unique secondary cell wall biosynthesis in flax and the directional selections on MYB46/MYB83 may have shaped the morphological profile of the current oil-use and fiber-use flax. [Display omitted] •Assemblies of genomes, including oil-use flax, fiber-use flax and pale flax•Comparative genomic analysis between pale flax and cultivated flax•Dual-selection mode on oil-use and fiber-use characteristics might be existing•Expansion and selection of MYB46/MYB83 may shape the morphological profile of flax Biological Sciences; Evolutionary Biology; Genomics; Plant Evolution; Plant Genetics